Optimization of reconstruction and quantification of motion-corrected coronary PET-CT - Doris, Mhairi K. (J Nucl Cardiol, 2018)
BACKGROUND: Coronary PET shows promise in the detection of high-risk atherosclerosis, but there remains a need to optimize imaging and reconstruction techniques. We investigated the impact of reconstruction parameters and cardiac motion-correction in (18)F Sodium Fluoride ((18)F-NaF) PET. METHODS: Twenty-two patients underwent (18)F-NaF PET within 22 days of an acute coronary syndrome. Optimal reconstruction parameters were determined in a subgroup of 6 patients. Motion-correction was performed on ECG-gated data of all patients with optimal reconstruction. Tracer uptake was quantified in culprit and reference lesions by computing signal-to-noise ratio (SNR) in diastolic, summed and motion-corrected images. RESULTS: Reconstruction using 24 subsets, 4 iterations, point-spread-function modelling, time of flight and 5-mm post-filtering provided the highest median SNR (31.5) compared to 4 iterations 0-mm (22.5), 8 iterations 0-mm (21.1) and 8 iterations 5-mm (25.6; all p<0.05). Motion-correction improved SNR of culprit lesions (n=33) (24.5[19.9–31.5]) compared to diastolic (15.7[12.4–18.1]; p<0.001) and summed data (22.1[18.9–29.2]; p<0.001). Motion-correction increased the SNR difference between culprit and reference lesions (10.9[6.3–12.6]) compared to diastolic (6.2[3.6–10.3]; p=0.001) and summed data (7.1 [4.8–11.6]; p=0.001). CONCLUSIONS: The number of iterations and extent of post-filtering has marked effects on coronary (18)F-NaF PET quantification. Cardiac motion-correction improves discrimination between culprit and reference lesions.